2016
DOI: 10.1017/s0031182016001864
|View full text |Cite
|
Sign up to set email alerts
|

Validation of droplet digital PCR for the detection and absolute quantification of Borrelia DNA in Ixodes scapularis ticks

Abstract: We evaluated the QX200 Droplet Digital PCR (ddPCR™, Bio-Rad) system and protocols for the detection of the tick-borne pathogens Borrelia burgdorferi and Borrelia miyamotoi in Ixodes scapularis nymphs and adults collected from North Truro, Massachusetts. Preliminary screening by nested PCR determined positive infection levels of 60% for B. burgdorferi in these ticks. To investigate the utility of ddPCR as a screening tool and to calculate the absolute number of bacterial genome copies in an infected tick, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Only recently have protocols been optimized for higher yield 35 . Meanwhile, the gut of an infected adult tick can harbor on average anywhere from 2,000 to over 50,000 Borrelia 37 38 39 , which is solidly within the detection range of nPCR. Thus, the protocol is well suited to tick surveillance efforts.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Only recently have protocols been optimized for higher yield 35 . Meanwhile, the gut of an infected adult tick can harbor on average anywhere from 2,000 to over 50,000 Borrelia 37 38 39 , which is solidly within the detection range of nPCR. Thus, the protocol is well suited to tick surveillance efforts.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the technique has been successfully applied in multiplex reactions to simultaneously detect a mammalian host gene 44 and other tick-borne pathogens 45 , which is not as readily achievable with nPCR. Other design modifications include droplet digital PCR (ddPCR) technology, which can quantify DNA without the use of a standard curve 39 48 . The lower detection limit of this technique for Borrelia is likewise around ten spirochetes/sample 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still an available test to confirm Lyme arthritis for its higher sensitivity to detect ospA DNA in synovial fluid [ 36 , 37 ]. Even though there is no reported application of ddPCR to the samples of patients with Lyme disease; recently, the potential advantages of ddPCR to detect the pathogens of Lyme disease in ticks were reported [ 38 ].…”
Section: Bringing Ddpcr Into Clinical Use For Infectious Disease Diagmentioning
confidence: 99%
“…Their results showed an increased sensitivity for the detection of M. tuberculosis DNA with ddPCR over qPCR and concluded that ddPCR might potentially be used as a non-invasive, rapid and highly sensitive diagnostics tool for the detection of both pulmonary and extrapulmonary tuberculosis. In another study by King et al 34 the authors used ddPCR for the detection and absolute quantification of Borrelia burgdorferi DNA in adult patients and Ixodes scapularis ticks. They concluded that ddPCR was as sensitive as a qPCR assay, but had some advantages over it, like fewer overall reactions and decreased sensitivity to PCR inhibitors.…”
Section: Digital Pcr -Application For Clinical Microbiologymentioning
confidence: 99%